Status and prospects of the ANZUS activity in the modern international legal context of the Asia-Pacific military-political security (International relations and international law Journal, 2016)
In this article, based on a comprehensive review and analysis of all the major stages of creation, formation and functioning of the ANZUS to generalize their findings in the content of military-political organization's activities to date. We consider the role of the South Pacific Nuclear Free Zone Treaty(Treaty of Rarotonga) general international legal context of the military-political arm of the ANZUS. It focuses on the prospects for its operation in relation to the positions of the two Member States ANZUS – Australia and the U.S., which is opposed to the official approach of another member state associations – New Zealand. Also, the author addresses the issues relating to the identification of serious problems, do not contribute to the further development of the integration model of military-political aspects of regional security.
Keywords: Asia-Pacific region; ANZUS; nuclear free zone; military and political security; Treaty of Rarotonga